Pengaruh Kebijakan Pemerintah, Kewirausahaan (Entrepreneur) terhadap Produktivitas Usaha dan Keberlanjutan (Sustainability) Pekebun Kecil pada Industri Kelapa Sawit di Provinsi Riau (Studi Pada Perkebunan Kelapa Sawit di Provinsi Riau) - Simatupang, Hinsatopa; Zain, Djumilah; Salim, Ubud; Armanu (Universitas Brawijaya, Indonesia, 2009)
The purpose of this research are fist : to know the relationship between entrepreneurship variables, government policies, the productivity of small farmers and the sustainability of small farmers activities in palm oil sector in Riau province. Second : to give the feed backs to the policy makers and agribusiness professionals, to enable them to maintain the growth and the development of ownership the small farmers in palm oil business. This research took 200 samples of small farmers in plasma project PIR and KPPA in 4 regencies in Riau province. For the purpose of the research, questionnaires were distributed to collect and analyze the relationship between the variables, Structural Equation Modeling (SEM) is used by applying the Analysis of Moment Structures Program ( AMOS). Several facts found in this research are, first; the government policy is adequate and supportive to the small farmers, it's only to increase the income and not to guide them to have the ability of entrepreneurship, second: the government policy applied to some of the small farmers is contra productive, where the facilities given make them weak and dependent. Third : The government policy can only grow the number of small farmers in this sector but fail to provide them with the mental of entrepreneurship and sustainability of the small palm business that the farmer is already start. Fourth : the small farmers have not yet understood the concept of environment friendly. The application of Roundtable on Sustainable Palm Oil (RSPO) by world consumers can boycott the palm oil product of small farmers which at the end will threat the sustainability of their business.